The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1080/09638288.2018.1498138
|View full text |Cite
|
Sign up to set email alerts
|

Even the fowl has feelings”: access to HIV information and services among persons with disabilities in Ghana, Uganda, and Zambia

Abstract: Background: Persons with disabilities have often been overlooked in the context of HIV and AIDS risk prevention and service provision. This paper explores access to and use of HIV information and services among persons with disabilities. Methods: We conducted a multi-country qualitative research study at urban and rural sites in Uganda, Zambia, and Ghana: three countries selected to exemplify different stages of the HIV response to persons with disabilities. We conducted key informant interviews with governmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…The findings from this study related to the multiple sources of stigma among persons with disabilities, including those living with HIV, have been reported elsewhere [26]. Briefly, the dual stigma of HIV and disability as well as the internalized stigma (i.e.…”
Section: Resultsmentioning
confidence: 65%
“…The findings from this study related to the multiple sources of stigma among persons with disabilities, including those living with HIV, have been reported elsewhere [26]. Briefly, the dual stigma of HIV and disability as well as the internalized stigma (i.e.…”
Section: Resultsmentioning
confidence: 65%
“…It shouldn't be seen as a stand-alone. [42] In fact, as illustrated by a number of the studies, people with different types of impairments described how they were excluded from health education campaigns or opportunities due to the initiatives only targeting the mainstream, or inclusion of disability being an afterthought [42,43,46,47,49,58]. Common examples included people with visual impairments not being able to see posters, billboards, or read informational pamphlets with health education messages, or people with hearing impairments not being able to hear messages broadcasted via radio or television programs [42,45,48,56].…”
Section: Informational Barriersmentioning
confidence: 99%
“…Some of these barriers are disability specific, depending on the type of impairments experienced. An example here is the absence of ramps for those with certain physical impairments resulting in difficulties entering the building, or lack of sign language interpreters for people with hearing impairment [38,41,45,48,49,54,[56][57][58]. This barrier is illustrated by an example of a person with visual impairment from Kenya, discussing the shortage or lack of sign language interpreters and guidance at the health facility:…”
Section: Practical and Logistical Barriersmentioning
confidence: 99%
“…Although people with disabilities require the same HIV/AIDS information, services and supports as all other members of society, they are excluded and neglected in all of the sectors responding to HIV and STI infections [ 3 ]. Remarkably, they are notably absent from equitable access and are often treated as a low priority for those services [ 8 , 9 ]. This access is hindered by several factors such as stigma and discrimination based on their disability status and/or type of disability.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature that recognizes a variety of issues that affect knowledge, attitudes, and practices in relation to HIV/AIDS and other STIs among people with disabilities. For example, a literature review from developing countries [ 10 ] and a research from Uganda [ 9 ] suggested that PWDs have very limited knowledge about HIV and other STIs because they are frequently excluded from access to HIV/AIDS and reproductive health information because of their disability status. Sociodemographic characteristics such as type of disability marital and educational level were also reported as potential predictors of knowledge and practices of PWDs in relation to HIV/AIDS because PWDs’ interest in seeking SRH-related services and information may be affected by these variables [ 5 , 11 ].…”
Section: Introductionmentioning
confidence: 99%